LEMBAGA PENDIDIKAN TINGGI ISLAM: HARAPAN, TANTANGAN, PARADIGMA, DAN PERANAN BAHASA ARAB - ABDUL HALIM HANAFI (IAIN Batusangkar, 2016)
Higher Education Institutions of Islamic: Hope, Challenges, Paradigms, and Role of Arabic. The 21 St Century Is The Age Globalization. It takes to impact on interdepedention, competition, and advances in science, information and commucation tecnology on institution of Islamic Higher Education. Interdepedention describe the somethink happened in a country correlated with other country. This condition has to change of paradigm at manajement of instituion higher education that the society make it is coorporate has to protecs and the best accuration and quickly servics to costomers. The problems are how the posision, condition, standarization, accuration, and protection of Islamic institutions higher education to servics costomers or student in Indonesia and how is learning system and developing science in this age. The aim of writing this paper will describe the problems and challenges facing Islmic institution of higher education and the expectations and strategies to deal accurationKata kunci: Pendidikan Tinggi, Mutu